Knowledge Spillovers from FDI: A Critical Review from the International Business Perspective. (1st December 2014) - Perri, Alessandra; Peruffo, Enzo
Abstract : This paper reviews and organizes the theoretical and empirical research on foreign direct investment (FDI) knowledge spillovers from the international business perspective. In doing so, it develops a framework for the analysis of this phenomenon. The suggested FDI knowledge spillover framework integrates both the macro‐level (country, industry, institutions) and micro‐level (multinational firm, headquarters, subsidiary, local firms) antecedents of spillovers with their consequences, and proposes to analyse spillovers along three main attributes that characterize their occurrence, i.e. their magnitude, scope and speed.